Analisis Kerusakan Bucket pada Mesin Grab yang Dapat Mempengaruhi Proses Bongkar Muat di Kapal MV. Nashalina - Mustofa, Jupri; Darmana, Eka; Pujianto, Fajar; ekadarmana, author (Politeknik Bumi Akpelni Semarang, 2026)
The hydraulic grab is an essential tool in cargo handling operations on bulk carrier vessels, particularly during coal loading activities at Muara Berau. In this study, a problem was identified when the Janus bucket hydraulic grab experienced damage that prevented it from closing properly, thereby disrupting the unloading process and causing operational delays. This research aims to identify the causes of the bucket hydraulic grab malfunction, explore solutions to overcome the issue, and formulate procedural maintenance steps in accordance with the manual book. The research employed a qualitative case study approach, combining direct observation onboard the vessel with in-depth interviews involving the ship’s engineer and electrician. The findings indicate that both internal and external factors contributed to the malfunction, including insufficient routine maintenance, piston seal leakage, severe rainfall, and forced unloading operations. These factors led to damage in several components such as receiver cables and solenoid valves, which showed reduced performance. The study concludes that strict and consistent application of maintenance procedures, as outlined in the manual book, is crucial to preventing similar failures and ensuring the reliability and efficiency of the hydraulic grab during cargo handling operations.